Neighborhood Guardianship and Property Crime Victimization. (May 2017) - Wickes, Rebecca; Zahnow, Renee; Schaefer, Lacey; Sparkes-Carroll, Michelle
In this study, we assess the extent to which the availability of guardians, guardianship expectations, and guardianship actions explain the variation of neighborhood property crime rates and self-reported property crime victimization. Furthermore, we examine whether or not the strength of these relationships is moderated by the neighborhood composition. We use data from the Australian Community Capacity Study (ACCS), a survey of 4, 000 respondents from 148 neighborhoods across Brisbane, Australia, and employ regression and multi-level regression techniques. We find that particular aspects of guardianship do protect against crime; however, the relationship between guardianship and crime is influenced by neighborhood diversity, disadvantage, and residential instability.